Accuracy, Authenticity, Fidelity: Aesthetic Realism, the "Deficit Model, " and the Public Understanding of Science. Issue 1 (27th March 2018) - Vidal, Fernando
Argument: "Deficit model" designates an outlook on the public understanding and communication of science that emphasizes scientific illiteracy and the need to educate the public. Though criticized, it is still widespread, especially among scientists. Its persistence is due not only to factors ranging from scientists' training to policy design, but also to the continuance of realism as an aesthetic criterion. This article examines the link between realism and the deficit model through discussions of neurology and psychiatry in fiction film, as well as through debates about historical movies and the cinematic adaptation of literature. It shows that different values and criteria tend to dominate the realist stance in different domains: accuracy for movies concerning neurology and psychiatry, authenticity for the historical film, and fidelity for adaptations of literature. Finally, contrary to the deficit model, it argues that the cinema is better characterized by a surplus of meaning than by informational shortcomings.